Assess Arrhythmia-causing excessive exercise using Holter Monitoring; Case Reports - Yusup Dwiyanto; Amelia Andini (Global Indonesia Health Care (GOICARE), 2024)
Exercise can indeed improve the quality of health if it is done in accordance with the rules or program. However, excessive exercise without considering the capacity of the organs, especially the heart, can result in disease, one of which is heart disease, namely heart rhythm disturbances. The death rate for athletes in 2022 will still be at 29% during competition. In this case, it proves that Holter monitoring (ambulatory ECG monitoring) is better in assessing heart rhythm in athletes. Arrhythmias in athletes are caused by inadequate cardiac remodeling, causing ion channels in the atrioventricular node to undergo immunohistochemical labeling, where L-type calcium (Ca2+) channels that carry inward current are known to play a major role in the diastolic depolarization of the atrioventricular node, and regulate the excitability and increase in axis potentiation. . In the important Ca2+ channels in the heart, a slowing process occurs which results in a barrier to atrioventricular node conduction. A decrease in the axis action potential phase process where calcium cannot replace potassium in cells results in electrical impulse disturbances.